The Effectiveness of CSR Programs in Banking Companies in Banda Aceh in Increasing Customer Loyalty - Sarno; Ardiansyah; Diman, Banta (Indonesian Journal Economic Review (IJER), 2024)
Corporate Social Responsibility (CSR) is a crucial strategy employed by financial institutions to enhance client connections. This study seeks to evaluate the efficacy of CSR initiatives executed by banking institutions in Banda Aceh in enhancing customer loyalty. The employed research method is a quantitative approach utilizing a survey design. Data were gathered via questionnaires administered to 50 respondents, comprising bank customers who have engaged with the CSR initiative. The analytical method employed linear regression to examine the correlation between customer perceptions of CSR and customer loyalty. The findings indicated that CSR initiatives substantially impact customer loyalty. Elements of CSR encompassing social responsibility towards society, environmental stewardship, and business ethics have been demonstrated to enhance customers' favorable opinions of the company. Respondents expressed significant gratitude for CSR projects in education and health. The findings also reveal that customer loyalty is not just driven by service quality, but also by a company's commitment to social and environmental sustainability. This study concludes that strategically relevant CSR programs can effectively enhance consumer loyalty. Banking enterprises in Banda Aceh are recommended to continue strengthening CSR initiatives with a sustainable and participatory approach, in order to produce greater social impact and preserve consumer trust and loyalty.